Como e quando o corpo fala: um correlato das respostas psicobiológicas frente ao estresse no voo-livre - Gomes de Assis Pimentel, Giuliano (2020)
In adventure sports, stress is a significant element, since each individual reacts to the risks, challenges and uncertainties of the environment. Within this topic, the study follows the most stressful moments in free-flight, interweaving the physiological reaction with the speech of the subjects studied, limiting the possibility of dialogue/confrontation between psychobiological and sociocultural data. They favored risky sports as a leisure option, practised by ordinary people who take adventure as a counterpoint to the tension and stress of everyday life. We carried out one-year direct observation and an interview with four pilots. In addition, we used the behavior of the measured heart rate of these subjects during the different stages of the free-flight. The results showed that the heart rate and the acute high residual levels are consistent with the story narrated by each person. The pilots proved that stress is a voltage required for the subsequent production of transcendent and pleasant feelings. In this sense, it is reflected that the security in the adventure experienced is the result of the equation between the psychophysiological activity and the subjective perception of risk.